Olive oil extraction optimization of ‘Galega Vulgar’ fruits by response surface methodology - Peres, Maria de Fátima (2017)
New strategies to attain better yields, without compromising olive oil quality, are necessary in olive oil extraction. To improve virgin olive oil yield, several processing aids (talc, calcium carbonate, salt, enzymes) have already been tested. ‘Galega Vulgar’, one of the most abundant Portuguese cultivar for olive oil, usually gives difficult pastes in the malaxation step, which represents a loss of income. The present work aimed to optimize olive oil extraction, at laboratory-scale, from fruits of ‘Galega Vulgar’ cultivar in 2016 (ripening index=4; moisture content=62 % and fat content (FW) =15.8 %) with the addition of processing aids (ProZym® and natural microtalc FC8-AW), using response surface methodologies (RSM). The combined effects of the concentrations of natural microtalc (MT) and of the enzyme preparation (E) on the oil extraction yield (Y), extractability index (IE), the concentration of total phenols (TPH), chlorophyll pigments (CP), as well as on chemical quality criteria parameters of the extracted olive oil, were investigated by RSM. A Central Composite Rotatable Design (CCRD) was followed, as a function of the contents of enzyme preparation (0-0.12 %, v/w) and of natural microtalc (0-0.46 %, w/w). For ‘Galega Vulgar’ olives, the highest extractability was obtained with simultaneous addition of enzymes between 0.02 and 0.08 % (v/w) and of microtalc (0.45-0.50 %, w/w).